Oxidative Damage to Nucleic Acids - Evans, Mark D.; Cooke, Marcus S.; SpringerLink (Online service) (New York, NY : Springer New York, 2007)
This book provides an up-to-date coverage of selected topics in the area of nucleic acid oxidation. The topics have been selected to cover everything from basic chemical mechanisms, repair of damage and the biological and pathological meaning of DNA oxidation. The chapters are authored by leading, research active, international experts in the respective topics. In addition to some of the traditionally covered topics, we have included some areas that receive less attention in similar volumes, for example chapters focusing on damage to nucleic acids by halogenating and nitrating species, gene-specific damage, telomere shortening and damage to promoter regions. Through this approach, we recognize additionally the importance of nucleic acid damage beyond mutation and in pathological conditions other than carcinogenesis. The primary audience for the book would be research scientists and advanced postgraduate students, the book may also be of interest to clinicians with strong research interests. We would expect readers to come away from this book with a greater appreciation of the topic, particularly appraising the reader of areas that may not necessarily have been covered in such a volume before.
Oxidatively Generated Damage to Cellular DNA: Mechanistic Aspects -- Chlorination and Nitration of DNA and Nucleic Acid Components -- Prevention of the Mutagenicity and Cytotoxicity of Oxidized Purine Nucleotides -- Nucleotide Incision Repair: An Alternative and Ubiquitous Pathway to Handle Oxidative DNA Damage -- OGG1: From Structural Analysis to the Knockout Mouse -- Processing of 3?-End Modified DNA Strand Breaks Induced by Oxidative Damage -- Oxidative Damage and Promoter Function -- Oxidative DNA Damage and Telomere Shortening -- Oxidative Damage and Repair in the Mitochondrial Genome -- The Role of Oxidative Damage to Nucleic Acids in the Pathogenesis of Neurological Disease -- Nucleic Acid Oxidation and the Pathogenesis of Cardiovascular Diseases -- Oxidative DNA Damage and Carcinogenesis -- The Physiological and Pathological Roles of Oxidative Damage to DNA in Relation to Life Stage -- Analysis of 8-Hydroxy-2?-Deoxyguanosine as a Marker of Oxidatively Damaged DNA in Relation to Carcinogenesis and Aging -- Oxidatively Damaged DNA and Inflammation -- The Role of Antioxidants in the Prevention of Oxidative Damage to Nucleic Acids.
Keywords: Life sciences; Biochemistry; Life Sciences; Biochemistry, general; Electronic books